As significações da educação física nas práticas docentes de uma professora - Oliveira, Renata Guisso de (2010)
The objective of this investigation was to understand the signification of the Physical Education of the school, on the teaching practice of a teacher, as also her point of view on these practices. This research has, as specific objective, to understand the practices in a dialog with the literature and to indicate pathways to new comprehensions about this occupation. Beyond this, aim to analyze how these practices allow giving a signification to the Physical Education in the researched school. Determining these objectives, makes out that the possible theory-methodological pathways would follow by the professional relationships area, that is why the study supports itself in the Sociology and Education, searching a dialog with the application area: Physical Education. By the collected data, identifies four “signification elements” to, from an interpretative analysis based in the axis occupation-teaching-identities, search for possible significations to the Physical Education. These elements are: the teacher-students relationship, the social and economical context, the question on identities and the commitment of the teacher with the occupation, with herself and with the area. About the teacher-students relationship, apprehend that this matter shows its complexities, but, in this context, it is fundamental to the teaching, and learning process of the students. On the social and economical context, recognize that this is a determinant factor to the actions of Sofia, and to the Physical Education signification, once that the collaborator intends to always convert her teaching practice according to the local reality aiming the providing of the students necessities. About the construction of the personal and professional construction of the personality of Sofia, understand that they are constantly (re)constructed from herself or from somebody else, having as an implication in the Physical Education the fact that the teaching, as a Professional intervention in the social practice, is closely imbricate with the identities of the subjects, in the proportion that of them are required ethical and political behavior in the professional development. On the commitment with the occupation, with herself and with the area, understand that the development of a good work with the Physical Education is related with the professional engagement with these three factors